2017
DOI: 10.1103/physreve.95.062138
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence between spanning trees and the Ising model on a square lattice

Abstract: An important problem in statistical physics concerns the fascinating connections between partition functions of lattice models studied in equilibrium statistical mechanics on the one hand and graph theoretical enumeration problems on the other hand. We investigate the nature of the relationship between the number of spanning trees and the partition function of the Ising model on the square lattice. The spanning tree generating function T (z) gives the spanning tree constant when evaluated at z = 1, while givin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…Guttmann and Rogers have defined a generating function that generalizes the spanning tree constant [12]. Subsequently, it was shown that this spanning tree generating function is related to the partition function of the isotropic Ising model in a precise way [13]. The connection is due to the fact that the same Mahler measure appears in both, which in turn is due to the random walk structure function for the square lattice.…”
Section: Discussionmentioning
confidence: 99%
“…Guttmann and Rogers have defined a generating function that generalizes the spanning tree constant [12]. Subsequently, it was shown that this spanning tree generating function is related to the partition function of the isotropic Ising model in a precise way [13]. The connection is due to the fact that the same Mahler measure appears in both, which in turn is due to the random walk structure function for the square lattice.…”
Section: Discussionmentioning
confidence: 99%
“…As reviewed in [21], the spanning tree constant is known to bear a close relation with the critical temperature T c in the Ising model. Moreover, it has been shown in [21]-using the STGF T(z)-which for two simple vertex-transitive lattices (square and triangular), this type of relation is also valid at any temperature value. So, legitimate questions would be: are there other physical models in which the STGF can map into some relevant quantity characterizing the systems?…”
Section: The Estgf and The Random Walk Loop Soup Modelmentioning
confidence: 99%
“…An illustrative example is the relation between the spanning tree constant z G of an infinite periodic graph G (for proper definitions, see section 2) and certain discrete spin-like models on G [19,20]. As explained in details in [21] (even with a brief historical account, refer to the references therein), for some problems like the Ising in the square lattice, the partition function at the critical temperature can be expressed as function of z sq .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations